2023
DOI: 10.24920/004120
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Microvascular Obstruction with Global and Regional Myocardial Function Determined by Cardiac Magnetic Resonance after ST-Segment Elevation Myocardial Infarction

Ya-Nan Zhao,
Jia-Ning Cui,
Xing-Hua Zhang
et al.

Abstract: Objective: To investigate the impact of microvascular obstruction (MVO) on the global and regional myocardial function by cardiac magnetic resonance feature-tracking (CMR-FT) in ST-segment-elevation myocardial infarction (STEMI) patients after percutaneous coronary intervention. Methods:Acute STEMI patients who underwent cardiac magnetic resonance at 1-7 days after successfully reperfusion were included in this retrospective study. Based on the presence or absence of MVO on late gadolinium enhancement images, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Bivalirudin yielded a lower incidence of IMH coinciding with decreased edema at the acute phase and one-month follow-up, which could herald an improved outcome after STEMI. The reduction in IMH could be attributed to bivalirudin’s direct thrombin inhibition, considering the role of thrombin-induced microvascular damage in IMH pathogenesis [ 37 ]. Our findings were consistent with other observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalirudin yielded a lower incidence of IMH coinciding with decreased edema at the acute phase and one-month follow-up, which could herald an improved outcome after STEMI. The reduction in IMH could be attributed to bivalirudin’s direct thrombin inhibition, considering the role of thrombin-induced microvascular damage in IMH pathogenesis [ 37 ]. Our findings were consistent with other observations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MVO are associated with adverse LV remodeling in reperfused STEMI patients [ 37 ]. IMH, a severe MVO outcome, has also been significantly linked with a decrease in LVEF in STEMI patients post-PCI [ 36 ].…”
Section: Discussionmentioning
confidence: 99%